Genetic resistance to malaria in mouse models - Hernández Valladares, M.; Naessens, Jan; Iraqi, F.A. (Elsevier, 2005)
Murine models have proved to be excellent tools in the support of studies of the human genetic bases of malaria resistance and have enabled the mapping of 12 resistance loci, eight of them controlling parasitic levels and four controlling cerebral malaria. Further studies using this method have identified a Pklr variant that confers resistance to murine malaria, a result that shows the potential of this approach to aid the understanding of mechanisms of disease resistance. In the future, the use of murine models for genetic resistance to malaria could lead to the identification of relevant genetic factors that control this devastating disease.